Analisis Perbaikan Efektivitas Dry Ash dan Wet Ash Unloader dengan Menggunakan Manufacturing Cycle Effectiveness - Harlinda Rasvi Nabela; Prasetyo (Fakultas Teknik dan Rekayasa, 2024)
Indonesia's need for electrical energy is also increasing along with increasing industrial activity. One of the power generating units that plays a vital role in Indonesia is the PLTU. PT. Bhimasena Power Indonesia is a PLTU company located in Batang, Central Java. The main fuel for electrical energy in PLTUs is coal. The transportation is carried out using trucks. However, due to limited parking space and a long unloader system, there are queues for truck transportation. Manufacturing Cycle Effectiveness calculations were carried out to determine the effectiveness value of the unloader system and then elimination of non-value added activities was carried out. It was found that the effectiveness percentage which was previously 51.6% became 55.3% after elimination, it could optimize the effectiveness value of the ash loading system at PT Bhimasena Power Indonesia.. Keywords: PLTU, Manufacturing Cycle effectiveness, Unloader.